Evaluation of the Effectiveness of the Intensive Mathematics Class Program through a Pretest-Posttest Study Using the Expository Method for Low Ability Students - Nata Atmadja, Hendrico Yehezky; Hidayani, Rahma (PT. Anagata Sembagi Education, 2025)
This study evaluates the effectiveness of the Intensive Mathematics Class Program (IMCP) - an expository teaching intervention designed to mitigate mathematics learning loss among low-achieving 10th-grade students at Sekolah Global Mandiri Cibubur, Indonesia, following by the fact of widespread COVID-19 educational disruptions (affecting 90% of learners globally) and documented declines in national PISA mathematics scores. Using a purposive sampling technique, 18 students with the lowest performance (three from each class) were selected to participate in structured instruction on quadratic equations, assessed through a pretest–posttest design. Results indicated significant improvement, with mean scores increasing from 1.33 (SD = 1.14) to 6.61 (SD = 3.47). Non-parametric tests (Shapiro–Wilk W = 0.806, p = 0.002) confirmed data non-normality and the effectiveness of the intervention, further supported by a large effect size, ES = 0.86. Notably, 17 out of 18 students demonstrated score improvements, while only 1 student showed no improvement. These findings show that systematic expository teaching can effectively bridge learning gaps. The study shows the effect of the IMCP as the strategy for low-achieving students in the post-pandemic context. However, the study’s generalizability is limited by its small sample size and localized setting in Senior High School Global Mandiri Cibubur. In the future, the research recommends to expand participant diversity and sample size.